Paradigma Baru Pendidikan di Era Society 5.0: Persepsi Mahasiswa terhadap Implementasi Kurikulum Merdeka - Tiara, Tiara; Nuriman, Nuriman; Sholekhah, Irmadatus; Islami, Novita Nurul (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
The policy of implementing MBKM is hope for universities so that they can adapt well to changing times, have a more positive impact on society, and provide extensive opportunities for universities to contribute to society. Concerning the implementation of a curriculum in higher education institutions, paying attention to student perceptions is considered to be important for assessing the effectiveness of implementing the curriculum as a learning reference from the perspective of the recipient object. Therefore, research was conducted to explore students' perceptions of implementing the Merdeka Curriculum. This research uses a mixed method with an explanatory sequential design. College students in East Java Province who have taken part in the Merdeka Curriculum program are the research population, and the sample is non-probability sampling with an accidental sampling technique. The data collection technique was carried out by distributing quantitative data questionnaires. The collected data is then triangulated to compare data obtained from various parties to ensure trust. The research results concluded that students' perceptions of technical indicators in MBKM learning were positive. Furthermore, students' perceptions of the MBKM learning process indicators, which contain three sub-indicators (interaction, teaching materials, and assignments), show positive results on average. Then, students' perceptions of the MBKM learning evaluation indicators, which contain four sub-indicators (mid-semester exam, final semester exam, learning outcomes, and sustainability), also show positive results.